Lectio Divina: Reading in The Rule of St Benedict. Issue 1 (April 2021) - Foster OSB, Dom David
Abstract : Classical traditions of reading lie at the origins of Lectio Divina, a characteristic practice of the Christian monastic tradition. The article is based on an analysis of the Prologue of the Benedictine Rule as a performative text, exemplifying the dynamic of the relationships between the human text and reader, as well as the sense of its authority in terms of divine authoriship as word of God, and how this dynamic creates a community of listeners and speakers. Lectio divina is thus presented as constitutive of the monastic community and the structures of authority that sustain it; the article shows how the Bible forms a monk's sense of time and existence. Finally it considers the Rule 's understanding of contemplation in a lived theology of reading.